The limited use of Dexmedetomidine for subarachnoid blocks in Pakistan - Muhammad Mubariz; Hira Hameed (Journal of the Pakistan Medical Association, 2023)
Respected Madam, Dexmedetomidine is a selective alpha-2 adrenoceptor agonist. It acts by binding to the presynaptic alpha-2 adrenoceptors and inhibits the release of norepinephrine. Thereafter, it causes a decrease in the sympathetic tone and terminates the propagation of pain signals. As a result, the haemodynamic and the endocrine stress responses of the body to surgery and anesthesia are attenuated, the blood pressure and heart rate are decreased, and the requirement for other anaesthetic agents is reduced. These effects have meant that dexmedetomidine has been widely used prior to endotracheal intubation to optimize the patients and prevent the likelihood of hemodynamic adverse effects (1). In addition to its use in general anesthesia, peri-operative physicians worldwide are now becoming increasingly aware of the dexmedetomidine’s potential usefor subarachnoid blocks. A few studies have documented the efficacy of intravenous (IV) dexmedetomidine in prolonging the duration of sensory and motor blockade induced by agents such as bupivacaine, prilocaine, and ropivacaine up to 4 hours (2), (3). Recent studies have found that intrathecal administration of dexmedetomidine in combination with the local anesthetic agent yields similar benefits (4). This has been attributed to the activation of presynaptic alpha2-A receptors at locus ceruleus and the termination of pain signal propagation via the medullospinal noradrenergic pathway (4). Therefore, it is no surprise that the use of dexmedetomidine in conjunction with local anesthetics for the subarachnoid block is common practice in peri-operative physicians throughout the globe. While Pakistani peri-operative physicians are aware of the benefits of dexmedetomidine prior to endotracheal intubation (5), the same cannot be said for subarachnoid blocks induced in Pakistan. Peri-operative physicians in Pakistan are either yet to realize the potential benefits the use of dexmedetomidine can provide for subarachnoid blocks or still adhere to conventional spinal anesthesia practices. Since the effects of a conventional subarachnoid block last from 2 to 3 hours, in any case of a surgical adverse event that prolongs the surgery, severe pain, nausea, vomiting, and derangement of the hemodynamic status have been noted in patients. Often times, this results in a shift towards general anesthesia midway through the procedure. Ultimately, the postoperative stay is prolonged which directly impacts the clinical outcome and the quality of life for these patients. —Continue